Reinterpreting Rāʿinā: A Maʿnā cum Maghzā Approach to Surah al-Baqarah [2]:104 and Its Relevance for Contemporary Communication Ethics - Azhar, SM. Fahmi; Hardimansyah; Indriastuti Ramadhani (Basmala: Journal of Qur’an and Hadith, 2025)
This study provides a comprehensive review of Surah al-Baqarah [2:104], focusing specifically on the prohibition of rāʿinā. It employs a maʿnā cum maghzā approach to address the shortcomings of classical interpretations, which often overlook the verse's modern relevance. This research argues that the verse serves as a foundational principle for communication ethics, safeguarding prophetic dignity and preserving social harmony in Medina. The study aims to construct a holistic understanding of the verse through an analysis of its historical meaning (al-maʿnā al-tārīkhī) and its historical-contemporary significance (al-maghzā al-tārīkhī and al-maghzā al-mutaḥarrik al-muʿāṣir). Utilizing linguistic, intratextual, intertextual, and socio-historical methods, this study reveals that the prohibition against rāʿinā was not due to its inherent negative connotations or foreign origins. Instead, it constituted a divine response to the deliberate misuse and semantic distortion of the term by certain Jewish groups who sought to insult the Prophet Muḥammad. Furthermore, these findings hold significant contemporary relevance as a Quranic principle for combating hate speech and promoting wasatiyyah (moderation) within pluralistic societies. This research contributes to Quranic studies by offering a deeper interpretation that challenges traditional views and provides a framework for addressing modern communication challenges. [Studi ini secara komprehensif meninjau Surah al-Baqarah [2]:104, khususnya larangan rāʿinā. Studi ini menggunakan pendekatan maʿnā cum maghzā untuk mengatasi kekurangan dalam interpretasi klasik yang sering mengabaikan relevansinya di era modern. Penelitian ini berargumen bahwa ayat tersebut berfungsi sebagai dasar etika komunikasi, melindungi martabat kenabian, dan menjaga harmoni sosial di Madinah. Tujuan penelitian ini adalah untuk membangun pemahaman holistik tentang ayat tersebut melalui analisis makna historis (al-maʿnā al-tārīkhī) dan signifikansi historis-kontemporernya (al-maghzā al-tārīkhī dan al-maghzā al-mutaḥarrik al-muʿāṣir). Dengan menggunakan metode linguistik, intratextual, intertextual, dan sosio-historis, studi ini mengungkapkan bahwa larangan terhadap rāʿinā bukan disebabkan oleh konotasi negatif yang melekat atau asal-usul asingnya, melainkan sebagai respons ilahi terhadap penyalahgunaan dan distorsi semantik yang disengaja oleh kelompok-kelompok Yahudi tertentu yang bertujuan untuk menghina Nabi Muḥammad. Selain itu, temuan ini sangat relevan saat ini sebagai prinsip Qur’ani untuk melawan ujaran kebencian dan mempromosikan wasatiyyah (moderasi) dalam masyarakat yang plural. Penelitian ini berkontribusi pada studi Al-Qur’an dengan menawarkan interpretasi yang lebih mendalam yang menantang pandangan tradisional dan menyediakan kerangka kerja untuk mengatasi tantangan komunikasi modern.]